KRITERIA PEMILIHAN JENIS KAYU SEBAGAI BAHAN BAKU ALAT MUSIK GAMBUS BERDASARKAN PERSEPSI MASYARAKAT DI KOTA PEKANBARU PROVINSI RIAU - Gemi Marta Jepri; M. Mardhiansyah '; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Melayu culturein Riau Provincecan be seen through of Riau traditional’s clothing, Riau traditional’s house, Riautypical’s food, Riautypical’s weapon, and traditional’s musical instrument. Generally,traditional’s musical instrumentin Riau usingwood raw material. One of them is gambus. There are many type of wood, but must be knownwhich of wood criteriais worthy for making gambus raw material musical instruments.Therefore it is necessary to did research about selecting criteria the type of wood as gambus raw material musical instrument based public perception in Pekanbaru City, Riau Province.This research aimed to identify selecting criteria the type of wood used as gambus raw material musical instrument.This research isqualitative research and data collection using survey method. Data collection techniquein this research did by retrieval of information through observation, interview and literature study. Analyze that used in this research is qualitative descriptive.Based on public perception in Pekanbaru City Riau Province, selecting criteria the type of wood that used as the main gambus raw material musical is jackfruit wood(Artocarpus heterophyllus), while the type of wood used as alternative raw material is acacia wood (Acaciamangium), mahogany wood (Swietenia macrophylla) and pulai wood (Alstonia scholaris). The wood criteria that used as raw material for making gambus is wood by diameter 35-40 cm, has no knots, and has wood straightness 80% - 100%. Keywords :Public perception, the type of wood, gambus musical instrument